Pulmonary sequelae in survivors of congenital diaphragmatic hernia. Issue 2 (February 1990) - Falconer, A R; Brown, R A; Helms, P; Gordon, I; Baron, J A
Abstract : Nineteen survivors of congenital diaphragmatic hernia repair were compared with age and sex matched control children six to 11 years after repair. All subjects were examined clinically and underwent lung function testing. The patients also had individual lung volumes assessed radiographically and had radionuclide (krypton-81 m, technetium-99 m macroaggregates) ventilation-perfusion (V/Q) lung scans. Four patients had pectus excavatum and two had mild scoliosis. Spirometric measurements were lower in the patients than in the control subjects but only the differences in peak expiratory flow and flow at 50% of expired vital capacity were significant. The radiographic left lung volumes in patients surviving left diaphragmatic repair were larger than expected at 49.3% (SD 2%), suggesting alveolar overdistension. V/Q scans showed a mismatch in the ipsilateral lung, mean Q (40% (7%] being significantly lower than mean V (47% (6%)). In seven patients who had required ventilation for four days or more perfusion to the ipsilateral lung was significantly lower (34% (6%)) than values for the 12 patients ventilated for less than four days (43% (6%)). Survivors of right diaphragmatic repair had a better outcome in terms of relative radiographic lung volumes and V/Q distribution. More severely affected children are now surviving repair of congenital diaphragmatic herniation, with residual pulmonary abnormalities that could produce functional impairment in adult life.